2020
DOI: 10.3390/jof6040218
|View full text |Cite
|
Sign up to set email alerts
|

Novel Colloidal Nanocarrier of Cetylpyridinium Chloride: Antifungal Activities on Candida Species and Cytotoxic Potential on Murine Fibroblasts

Abstract: Nanocarriers have been used as alternative tools to overcome the resistance of Candida species to conventional treatments. This study prepared a nanocarrier of cetylpyridinium chloride (CPC) using iron oxide nanoparticles (IONPs) conjugated with chitosan (CS), and assessed its antifungal and cytotoxic effects. CPC was immobilized on CS-coated IONPs, and the nanocarrier was physico-chemically characterized. Antifungal effects were determined on planktonic cells of Candida albicans and Candida glabrata (by minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
3
9
0
Order By: Relevance
“…Although a previous study found that IONPs and CS alone led to marked reductions in the viability of L929 cells for concentrations from 87.5 and 175 µg/mL, respectively [25], these compounds did not potentiate the cytotoxic effects of the IONPs-CS-FLZ and IONPs-CS-MCZ nanocarriers. In fact, the results of the present study indicate that the nanocarriers' cytotoxicity is primarily dependent on the presence of the antifungals (FLZ and MCZ), corroborating a previous study in which the cytotoxicity of a cetylpyridinium chloride nanocarrier was also dependent on the presence of the drug, with no influence of the carrier compound (IONPs-CS) [26].…”
Section: Discussionsupporting
confidence: 91%
“…Although a previous study found that IONPs and CS alone led to marked reductions in the viability of L929 cells for concentrations from 87.5 and 175 µg/mL, respectively [25], these compounds did not potentiate the cytotoxic effects of the IONPs-CS-FLZ and IONPs-CS-MCZ nanocarriers. In fact, the results of the present study indicate that the nanocarriers' cytotoxicity is primarily dependent on the presence of the antifungals (FLZ and MCZ), corroborating a previous study in which the cytotoxicity of a cetylpyridinium chloride nanocarrier was also dependent on the presence of the drug, with no influence of the carrier compound (IONPs-CS) [26].…”
Section: Discussionsupporting
confidence: 91%
“…From the calibration curve, determined on the basis of cytotoxicity evaluation in the interval from 0.25 to 3 µg.mL −1 of pure HDP (R 2 = 0.9911), it can be estimated that approximately 2.5 µg.mL −1 HDP was extracted from the composite into the leachate. The cytotoxic potential of HDP has also been reported by other authors (Mûller et al, 2017;Araujo et al, 2020;Kanno et al, 2020).…”
Section: -(45-dimethylthiazol-2-yl)-25-diphenyltetrazolium Bromide Vi...supporting
confidence: 75%
“…There have been efforts ranging from the use of over-the-counter cleansing agents and surfactants [ 32 , 33 ], to employing electrostatic interactions to reduce adhesion [ 5 , 12 , 17 , 25 , 26 , 27 ], along with combinations of charge alteration and antimicrobial loading [ 16 , 34 ]. More recently nanotechnology is being employed with titanium dioxide [ 29 ] or silver [ 35 ] incorporated within PMMA polymers as well as the development of CPC in a colloidal nanocarrier of Chitosan and Iron Oxide [ 36 ].…”
Section: Discussionmentioning
confidence: 99%